2018
DOI: 10.1561/1500000034
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Information Retrieval: Progress and Challenges in Spatial Search of Text

Abstract: Significant amounts of information available today contain references to places on earth. Traditionally such information has been held as structured data and was the concern of Geographic Information Systems (GIS). However, increasing amounts of data in the form of unstructured text are available for indexing and retrieval that also contain spatial references. This monograph describes the field of Geographic Information Retrieval (GIR) that seeks to develop spatially-aware search systems and support user's geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 153 publications
0
29
0
Order By: Relevance
“…Besides, Table 7 suggests that (iii) Hausdorff distance as spatial similarity metric produces slightly better results than area of overlap (s6 and s7 left aside) from the user's viewpoint. As regards the method, previous work has indicated that a "challenge for future research in GIR, and more particularly georeferencing, is reproducible publishing of methods, algorithms, datasets, and results such that approaches can be more easily compared across corpora" ( [53], emphasis added). The method used in this work has involved two key steps towards a holistic assessment of spatial search strategies, namely performance-based and user-based assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Table 7 suggests that (iii) Hausdorff distance as spatial similarity metric produces slightly better results than area of overlap (s6 and s7 left aside) from the user's viewpoint. As regards the method, previous work has indicated that a "challenge for future research in GIR, and more particularly georeferencing, is reproducible publishing of methods, algorithms, datasets, and results such that approaches can be more easily compared across corpora" ( [53], emphasis added). The method used in this work has involved two key steps towards a holistic assessment of spatial search strategies, namely performance-based and user-based assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic information retrieval (GIR) [142,143] is another relevant field which deals with the automated interpretation of place names and spatial relationships in queries and in documents and with indexing, relevance ranking, and retrieval of the relevant content. GIR faces significant challenges such as detecting geographical references and associated spatial natural language qualifiers, disambiguating place names or other geographic information, and ranking resources with respect to spatial, temporal, and thematic relevance.…”
Section: Semantic Search and Knowledge Discoverymentioning
confidence: 99%
“…-students of computer science, especially in information retrieval, who want to learn about mobility-relevant spatial computation around search/IR (e.g. [2]); -practicing IR engineers who would like to expand their areas of expertise so as to include geographic search; -information retrieval researchers interested in and introduction and state-ofthe-art review [14] on GIR and Geo-NLP; -geographers or GIS experts who have not yet worked with text, and who would like to learn how the spatial knowledge implicit in text collections can be used to support geospatial analysis.…”
Section: Target Audiencementioning
confidence: 99%
“…Together with Chris Jones, he organises the workshop on Geographic Information Retrieval which has been hosted by CIKM, SIGIR and ACM SIGSPATIAL, and which has been an important incubator of many ideas related to GIR. He recently co-authored a comprehensive review of GIR [14].…”
Section: Katherine Mcdonough Is a Senior Research Associate At The Almentioning
confidence: 99%